Peran lnfluencer Media Sosial Membentuk Opini Publik di Kalangan Mahasiswa - Andiny Putri Vanosha; Azizah Azizah; Febrian Febrian; Greshela Putrinova; Hafizah Luthfiyyah; Hayatul Fazila; Juseradovi Triadi; Latifah Hanum Harahap; M. Rafi Ardiansah; Muhammad Rafi; Perawati Perawati (Studi Administrasi Publik dan ilmu Komunikasi, 2026)
This study aims to comprehensively examine the role of social media influencers in shaping public opinion among university students through a literature review approach. The background of this research is based on the rapid development of information technology and social media, which has given rise to influencers as new communication actors with strong influence in the digital public sphere. Influencers act as opinion leaders who not only deliver information but also frame messages, construct narratives, and disseminate various issues to their audiences. University students are selected as the focus of this study because they represent an active, critical group of social media users who are highly exposed to digital content. The research method employs a literature review by analyzing various national and international scholarly journals relevant to the topics of influencers, social media, and public opinion formation. The findings indicate that influencers have a significant impact on shaping students’ mindsets, attitudes, perceptions, and attention toward social, political, cultural, and lifestyle issues. Factors such as credibility, popularity, and the intensity of interaction between influencers and their audiences play an important role in determining the effectiveness of this influence. Based on these findings, it can be concluded that social media influencers play a strategic and increasingly dominant role in the process of public opinion formation among university students in the era of digital communication.